„Przybędą ze wschodu i zachodu [...]”. Augustyńska interpretacja Mt 8,11 i Łk 13,28-29 na tle starożytnej egzegezy - Nieścior, Leon (Annales Missiologici Posnanienses, 2014)
The article offers a complete overview of the Greek and Latin patristic exegesis of Mt 8,11 and Lk 13,28-29 with special focus on the exegetical commentaries of St. Augustine. Church Fathers underlined the ecclesiological dimension of Christ’s eschatological promise. According to St. Augustine and other theologians, those who come “from east and west” are above all pagans who through faith and baptism become members of the Church. Some focus more on the stage of maturation of the Christian faith, thus those who “come from east and west” are the just and holy Christians who have perfected their faith. There is a difference of opinion between Origene and Augustine concerning the word „many”. It should be analyzed in the broader context of their reflections on the universality of salvation. Secondly, the patristic exegesis underlines the eschatological aspect of Christ’ promise. The feast with the patriarchs symbolizes common heritage of faith and Christ is seen as the one who invites all the participants. Thirdly, there is a paranetical aspect of the patristic exegesis. Church Fathers expressed their reflections in the pastoral context, in homilies and spiritual conferences. They point to the quality of the humble faith of the centurion of Capharnaum, which guarantees a future participation in the eschatological feast with the patriarchs.